Existence of Almost-Periodic Solutions for Lotka-Volterra Cooperative Systems with Time Delay - Kaihong Zhao (Journal of Applied Mathematics)
This paper considers the existence of positive almost-periodic solutions for almost-periodic Lotka-Volterra cooperative system with time delay. By using Mawhin’s continuation theorem of coincidence degree theory, sufficient conditions for the existence of positive almost-periodic solutions are obtained. An example and its simulation figure are given to illustrate the effectiveness of our results.